SOCIAL RESPONSIBILITY : KAJIAN THEORETICAL FRAMEWORK, DAN PERANNYA DALAM RISET DIBIDANG AKUNTANSI - Nor Hadi (Universitas Wahid Hasyim, 2009)
Past decades, the issue of corporate social responsibility very debated, demanding move corporate orientation from shareholder to stakeholder orientation. Implementation of social responaibility, described in social theories such as ethics theory, legitimacy theory, stakeholder theory, contracting theory, political theory and much more. In the perspective of legitimacy theory, companies existancies can not avoid the existence of stakeholders who are the parties to the mutual influence of the company. To that end, the company must maintain the congruence of interests between the company-of stakeholders (stakeholder theory).Corporate social responsibility is increasingly penetrated by no limits, apparently has an important role in the development of accounting, which is increasingly rampant social accounting studies (social accounting). That, of giving legitimacy of accounting as a social science that is open to the development of field phenomenon. The real manifestation of accounting response to social issues is increasingly widespread social studies Consequences of disclosure in relation to economics. Most developments do not question the aspect of social accounting matters: (a) why the company conducts social reported; (b) what are the social content of the report gives the signal to company performance, (3) what are the dimensions of corporate social performance measures, (4) whether effective enough social responsibility and meet the expectations of stakeholders, and (5) whether the most appropriate approach in the implementation of social responsibility.Key words: Corporate Social Responsibility, legitimation, stakeholder